Self-Efficacy, Proxy Efficacy, Media Literacy, and Official Media Use in COVID-19 Pandemic in China: A Moderated Mediation Model - Li, Qingrui; Zheng, Yu; Zhang, Junqing; Geng, Rui (Frontiers in Psychology, 2022)
Purpose: Covid-19 pandemic is a significant threat towards the public health. However, the discussion of the mechanism of media literacy’s effect in fighting against pandemic is limited. Thus, this study aims to explore the mechanism with a sociocognitive perspective. Methods: A survey was administrated to 420 college students in China. PROCESS macro of SPSS was applied to analyze the data and test the moderated mediation effect. Results: The moderated mediation model of media literacy, proxy efficacy, self-efficacy and official media use was tested and supported. Official media use was a negative moderator on the association between media literacy and proxy efficacy. Conclusion: The study explored the media literacy’s role as a determinant of proxy efficacy and self-efficacy, which contributed to the sociocognitive theory.